2020
DOI: 10.18325/jkmr.2020.30.4.119
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Carpal Tunnel Syndrome in Traditional Chinese Medicine: Using China National Knowledge Infrastructure Database

Abstract: Objective The purpose of this study was to investigate clinical studies between 2015 and 2020 on the traditional Chinese medicine treatment for carpal tunnel syndrome (CTS) using the China National Knowledge Infrastructure (CNKI) database. Methods We searched clinical studies on the Chinese medicine treatment published in traditional Chinese medical journals on CTS through the CNKI search. Fifteen published studies between 2015 and 2020 were chosen and examined for the year of publication, sample size, study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Korean traditional medical treatments for CTS typically include acupuncture, although studies have contradictorily demonstrated the superior and inferior efficacy of acupuncture to placebo or sham acupuncture [ 11 ]. Korean studies of acupuncture for CTS include a randomized control trial (RCT) that compared the effectiveness of Sweet Bee Venom pharmacopuncture to that of Scolopendrid pharmacopuncture, case reports of pharmacopuncture (CA; Scolopendrid , Carthmi-Flos , and Sweet Bee Venom, along with Jungsongouhyul and Hwangryunhaedok-tang pharmacopunctures) and acupotomy, and papers on acupuncture-based treatment [ 12 , 13 ]. Systematic reviews (SR) of Korean medical treatments, including acupuncture, for CTS were conducted [ 11 , 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Korean traditional medical treatments for CTS typically include acupuncture, although studies have contradictorily demonstrated the superior and inferior efficacy of acupuncture to placebo or sham acupuncture [ 11 ]. Korean studies of acupuncture for CTS include a randomized control trial (RCT) that compared the effectiveness of Sweet Bee Venom pharmacopuncture to that of Scolopendrid pharmacopuncture, case reports of pharmacopuncture (CA; Scolopendrid , Carthmi-Flos , and Sweet Bee Venom, along with Jungsongouhyul and Hwangryunhaedok-tang pharmacopunctures) and acupotomy, and papers on acupuncture-based treatment [ 12 , 13 ]. Systematic reviews (SR) of Korean medical treatments, including acupuncture, for CTS were conducted [ 11 , 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%